Prolactin/growth hormone–derived antiangiogenic peptides highlight a potential role of tilted peptides in angiogenesis - Nguyen, Ngoc-Quynh-Nhu (National Academy of Sciences, 2006)
Angiogenesis is a crucial step in many pathologies, including tumor growth and metastasis. Here, we show that tilted peptides exert antiangiogenic activity. Tilted (or oblique-oriented) peptides are short peptides known to destabilize membranes and lipid cores and characterized by an asymmetric distribution of hydrophobic residues along the axis when helical. We have previously shown that 16-kDa fragments of the human prolactin/growth hormone (PRL/GH) family members are potent angiogenesis inhibitors. Here, we demonstrate that all these fragments possess a 14-aa sequence having the characteristics of a tilted peptide. The tilted peptides of human prolactin and human growth hormone induce endothelial cell apoptosis, inhibit endothelial cell proliferation, and inhibit capillary formation both in vitro and in vivo. These antiangiogenic effects are abolished when the peptides' hydrophobicity gradient is altered by mutation. We further demonstrate that the well known tilted peptides of simian immunodeficiency virus gp32 and Alzheimer's β-amyloid peptide are also angiogenesis inhibitors. Taken together, these results point to a potential new role for tilted peptides in regulating angiogenesis.